Intertextuality and the Book of Revelation in the Slovene Translation of Bulgakov’s The White Guard - Kaloh Vid, Natalia; Koletnik, Mihaela (Slavia Centralis, 2023)
The first part of the research presents the works of one of the greatest contemporary Russian writers, Mikhail Afanisiejvich Bulgakov while further on focusing on the analysis of intertextual devices that Bulgakov uses to establish intertextual connections between his first novel The White Guard and the apocalyptic Book of Revelation in the only Slovene translation by Marjan Poljanec (1973). The numerous allusions and direct quotes from the Book of Revelation convey a special meaning attributed to the apocalyptic text in Bulgakov’s masterpiece. The present paper is interested in the extent, if there is any, to which the intertextual elements are preserved in the Slovene translation and which strategies Poljanec used to preserve them.
Keywords: Bulgakov, White Guard, Revelation, intertextuality, allusion, history